PENGARUH KUALITAS PELAYANAN, PROMOSI, DAN LOKASI TERHADAP KEPUASAN PELANGGAN BANQUET ROOM HOTEL LE GRANDEUR JAKARTA - Hanifan Cahyo Nugroho; Prawoto (LPPM Universitas Asa Indonesia, 2019)
Purpose- This study aims to determine the effect of service quality, promotion, and location on customer satisfaction banquet room Hotel Le Grandeur Jakarta partially or simultaneously. Design/methology/approach The population in this study were customers of the Hotel Le Grandeur Jakarta. The sample was determined using the Purposive Sampling method. The type of data used in this study is primary data, namely 100 questionnaires distributed to customers from the Hotel Le Grandeur Jakarta. Data were processed using multiple regression analysis with the help of SPSS v20 for windows. Findings- The results of this study indicate that partially service quality, promotion, and location variables were significantly influence customer satisfaction partially and simultaneously.